Gastric Trichobezoar: A Case Report - Shamsad, Sadia; Karim, Md Shahid; Chowdhury, Lutful L (Pulse, 2024)
Trichobezoar is a rare disorder that almost exclusively affects young females. Up to 90% of the patients range between 13 to 20 years of age. It consists of a compact mass of hair occupying the gastric cavity to a various extent. When the trichobezoar extends past the duodenum it is better called Rapunzel Syndrome.We are reporting a case of a 13-yearold girl, who presented with complaints of Upper abdominal pain for 5 days with vomiting several times over the same duration. She had a history of several episodes of similar symptoms from early childhood and was admitted in different hospitals several times and was treated conservatively. Clinical examination showed tenderness and hard mass over the epigastric region, extending towards the right hypochondriac region. Endoscopy revealed that there was a giant trichobezoar impacted from the fundus all the way to pylorus of stomach. CT scan results also showed that the stomach was filled with large intra-luminal abnormal mass like contents with mottled air pattern extended from fundus to fill the pylorus. laparotomy was performed to remove the bezoar successfully. This case report highlights the importance of early diagnosis of trichotillomania and trichobezoar and treatment of both by surgically along with medical management by medication and counselling of the patient and family members. Pulse Vol.16, 2024 P: 38-42